Orobanche bohemica Čelak. (Orobanchaceae) at the eastern limit of its geographical range: new data on its distribution in Poland - Piwowarczyk, Renata (Biodiversity: Research and Conservation, 2012)
A new locality of Orobanche bohemica Čelak., one of the rarest representatives of the family Orobanchaceae in Central and South-Western Europe, is reported from Poland. This is the first confirmed record of the species in Poland. It is the easternmost site known for the species, so it extends its distribution range. The species was recorded in Zawiercie-Bzów in the Czȩstochowa Upland (Wyżyna Czȩstochowska) in July 2010. Its host, abundance, and habitat preferences at the new locality are described, and a supplemented map of its distribution in Europe and Poland is given. Its taxonomic position as well as some diagnostic features that distinguish O.bohemica from O.purpurea are also discussed.